Genetic evidence for partial redundancy between the arginine methyltransferases CARM1 and PRMT6 - Cheng, Donghang (J Biol Chem, 2020)
CARM1 is a protein arginine methyltransferase (PRMT) that acts as a coactivator in a number of transcriptional programs. CARM1 orchestrates this coactivator activity in part by depositing the H3R17me2a histone mark in the vicinity of gene promoters that it regulates. However, the gross levels of H3R17me2a in CARM1 KO mice did not significantly decrease, indicating that other PRMT(s) may compensate for this loss. We thus performed a screen of type I PRMTs, which revealed that PRMT6 can also deposit the H3R17me2a mark in vitro. CARM1 knockout mice are perinatally lethal and display a reduced fetal size, whereas PRMT6 null mice are viable, which permits the generation of double knockouts. Embryos that are null for both CARM1 and PRMT6 are noticeably smaller than CARM1 null embryos, providing in vivo evidence of redundancy. Mouse embryonic fibroblasts (MEFs) from the double knockout embryos display an absence of the H3R17me2a mark during mitosis and increased signs of DNA damage. Moreover, using the combination of CARM1 and PRMT6 inhibitors suppresses the cell proliferation of WT MEFs, suggesting a synergistic effect between CARM1 and PRMT6 inhibitions. These studies provide direct evidence that PRMT6 also deposits the H3R17me2a mark and acts redundantly with CARM1.